The Modrating Role of Dynamic Knowledge capabilies in Addressing Organizational Failures to Achieve Business Competitiveness: Applied Research in Dairy Industries - الكبيسي, صلاح الدين عواد; غالب, الاء عبد الكريم (Journal of Economics and Administrative Sciences, 2019)
Purpose/ to build clear perceptions about the level of the effects of organizational failures on the competitiveness of dairy factories and the role of dynamic knowledge capabilities in minimizing these impactsMythology/ Design approach Use deduction approach, the research was conducted in four dairy factories in Baghdad (Abu Ghraib, Agriculture, Halal and Ayon Al-Rafidain). It was applied to a sample of (155) individuals representing a sample of the research community from factory owners, managers, Engineers, technicians and experienced workers in the dairy industry. The questionnaire was used as a main tool for collecting data, information and statistical tools in the extraction, testing and analysis of results.Finding/ It was found that having communication capabilities enable to mitigate the negative impact of organizational failures in competitiveness.Practical implications/ enhancing the dynamic knowledge capabilities of dairy plants will contribute to reducing the causes of organizational failures and thus increase their competitiveness.Value/ originality Enriches the literature of strategic management, organizational behavior and knowledge management that contribute to the search for how and why to reduce the dynamic knowledge capabilities of the negative effects of organizational failures in competitivenessPaper type/ survey research